A Pragma-Stylistic Analysis of Nigeria’s President Bola Ahmed Tinubu’s Inaugural Speech - Franck Amoussou; Ayodele Adebayo Allagbe; Coffi Martinien Zounhin Toboula (International Journal of Educational and Psychological Sciences, 2024)
This paper sets out to look into some pragmatic and stylistic resources deployed in the Nigeria’s newly elected president’s, Bola Ahmed Tinubu’s, inaugural speech. Drawing its theoretical underpinnings from pragma-stylistics propounded by Black (2006), it specifically seeks to examine such features as speech acts, tenses, deictic expressions, and tropes encoded in the speech. The findings arrived at reveal that the aforementioned politician employs four out of the five illocutionary acts (representatives, expressives, commissives, and directives) in varying proportions. They also disclose that the simple present, present perfect, simple past, simple future and imperative are the tenses deliberately deployed in the discourse. It is inferred from the foregoing that in his choice of discursive patterns, Tinubu plainly focuses on the socio-political, socio-economic and geo-political context to manipulate linguistic resources for ideological purposes in order to (i) restore Nigerians’ trust and faith in his forthcoming governance, (ii) persuade the audience, and overall (iii) manage his message for effective communication.